Rapid Brain Death following Cardiac Arrest without Intracranial Pressure Rise and Cerebral Circulation Arrest - Maxime Nguyen; Thomas Bièvre; Abdelouaid Nadji; Bélaïd Bouhemad (Case Reports in Critical Care)
We describe here an unusual case of brain death following cardiac arrest. Brain electric activity had totally ceased, allowing the confirmation of brain death, despite normal cerebral blood flow (assessed by both transcranial doppler and tomodensitometry) and no evidence of intracranial hypertension. In our case, a residual electric activity was assessed at admission and lesions worsened on imaging during ICU stay, suggesting that part of the neuronal damage occurred after brain reperfusion. All these elements suggest BD rather by cellular toxicity than intracranial pressure elevation.